CERUCUK BAMBU SEBAGAI MITIGASI BENCANA BANJIR PADA WILAYAH DARATAN DI SUNGAI SAPIH, KOTA PADANG - Irwan Irwan; Zelfi Syafioda Yenti; Firtia Bela Ananda (Republic of Indonesia Defense University, 2023)
The flood that occurred on Air Paku Street, Kuranji Subdistrict, Sungai Sapih Village, Padang City caused many losses to the people on Air Paku Street. The community experienced many impacts from the flood. This study aims to determine what mitigation is done by residents in overcoming flooding on Jalan Air Paku, Kuranji sub-district, Sungai Sapih village, Padang city. The approach used in this research is a qualitative approach. Data collection techniques through 2 stages, namely: observation and interviews with affected communities. The data analysis used is the analysis model of Miles Huberman. The results of the study indicate that flooding is very impactful for the community because houses, roads, schools and even residents' rice fields are also affected by flooding. The effort made by the community is to build a bamboo niche as a flood mitigation.